Codes applicability of estimating the FRC compressive strength by the core-drilling method. (2nd May 2022) - Taman, Mohamed; Abd Elaty, Metwally; Behiry, Reda N.
Highlights: The core-drilling method is a reliable test to evaluate the compressive strength. The FRC compressive strength was estimated by the core-drilling method. The existing relationships underestimate the core compressive strength for FRC. A new modification factor was proposed. Abstract: The core-drilling method is a reliable and confident method to evaluate the in-situ compressive strength. Codes and standard relations are developed to evaluate the compressive strength of the traditional concrete. The fiber reinforced concrete (FRC) is different in its behavior and mode of failure when compared to traditional concrete. This paper presents an experimental study on the applicability of these features of FRC. 168 drilled specimens were extracted from 10 different concrete mixes then tested. The investigated parameters were: the fiber type (polypropylene, glass, steel); fiber volume fraction (0.25%, 0.50%, 0.75%); cutting direction (horizontal, vertical); core diameter (100 mm, 150 mm). Standard cubes and cylinders were taken from each mix to evaluate the compressive strength. The results of the drilled cores were verified to more than predicted by code. The results revealed that the existing relationships underestimate the core compressive strength for FRC. A new modification factor was proposed depending on the fiber type and fiber volume fraction to estimate accurately the in-situ core compressive strength.